Persepsi Remaja Putri tentang Kanker Serviks : Teori Health Belief Model - Harwati, Andriati Reny (Universitas Malahayati, 2023)
ABSTRACT Cervical cancer is a malignancy that attacks the reproductive system in women. The aim of this research is to determine the perceptions of young women about cervical cancer and efforts to prevent it using the Health Belief Model (HBM) theory approach. This research design uses a descriptive quantitative study with a cross sectional approach. The sampling technique used was purposive sampling with a total sample of 162 respondents. The results of this study showed that the majority of respondents were 17 years old (48.1%), the majority of respondents had a positive perception of the susceptibility of cervical cancer (53.1%), the majority of respondents had a positive perception of the severity of cervical cancer (61.7%). %), the majority of respondents had a positive perception of the benefits of preventing cervical cancer (56.2%), the majority of respondents had a negative perception of the barriers (69.1%), the majority of respondents had a positive perception of their self-efficacy to prevent cervical cancer (72.2%) and the majority of respondents had a positive perception of cervical cancer and its prevention efforts (53.7%). Efforts are needed to increase positive perceptions of cervical cancer among young women, one of which is through providing health information about cervical cancer and how to prevent it. Keywords: Health Belief Model, Cervical Cancer, Perception, Teenagers ABSTRAK Kanker serviks merupakan salah satu keganasan yang menyerang sistem reproduksi pada wanita. Tujuan penelitian ini adalah untuk mengetahui persepsi remaja putri tentang penyakit kanker serviks serta upaya pencegahnnya dengan menggunakan pendekatan Teori Health Belief Model (HBM). Desain penelitian ini menggunakan studi kuantitatif deskriptif dengan pendekatan cross sectional. Teknik sampling yang digunakan adalah purposive sampling dengan jumlah sampel sebanyak 162 responden. Hasil penelitian ini diketahui bahwa sebagian besar responden berusia 17 tahun (48,1%), sebagian besar responden memiliki persepsi positif terhadap kerentanan penyakit kanker serviks (53,1%), sebagian besar responden mempunyai persepsi positif terhadap keparahan kanker serviks (61,7%), sebagian besar responden memiliki persepsi positif terhadap manfaat pencegahan kanker serviks (56,2%), sebagian besar responden mempunyai persepsi negatif terhadap hambatan (69,1%), mayoritas responden memiliki persepsi positif terhadap keyakinan diri untuk melakukan pencegahan kanker serviks (72.2%) dan sebagian besar responden mempunyai persepsi positif terhadap kanker serviks beserta upaya pencegahannya (53.7%). Diperlukan upaya untuk meningkatkan persepsi positif terhadap kanker serviks pada remaja putri, salah satunya melalui kegiatan pemberian informasi kesehatan tentang penyakit kanker serviks beserta cara pencegahannya. Kata Kunci: Health Belief Model, Kanker Serviks, Persepsi, Remaja